Predictive analysis of the influence of teachers’ proactive classroom management strategies on students’ disruptive behaviours - Ekundayo, Doyin Adebola; Alade, Muhammad Miftah (Universitas Kanjuruhan Malang, 2025)
In recent years, school disruption remains a clog in the wheel of school success. Different approaches are being adopted to manage it. This study aimed to examine the predictive role of teachers’ proactive management measures by classroom management behaviour and consistency discipline on students’ disruptive behaviours in secondary schools in Lagos, Nigeria. A quantitative research design was used, and 367 teachers responded to the questionnaires. Meanwhile, the self-designed questionnaire was validated and subjected to reliability with Cronbach’s alpha coefficient of 0.69. The statistical package for social sciences aided the analysis of the data collected. It was found that consistency discipline (0.264 <0.01) while management behaviour did not. It was therefore suggested that training on the effective use of proactive classroom management strategies.